The financial risk and performance of Swedish SRI funds - Hallquist, Lukas (2018)
This study addresses the existing issue of SRI fund categorization in previous research by establishing a framework of how to classify SRI funds. Through this framework, the SRI fund performance analysis becomes more accurate by evaluating the eﬀects of diﬀerent SRI strategies. In contrast to previous research, this study ﬁnds that SRI funds behave diﬀerently from conventional funds in terms of risk and return. The evidence suggests SRI funds that excludes sin industries from their investment portfolios have higher risk-adjusted returns than conventional funds.